KLASIFIKASI KOMUNITAS BURUNG DICAGAR ALAM GUNUNG TINOMBALA KECAMATAN MEPANGA KABUPATEN PARIGI MOUTONG - Miranda, Tyas; M., Sri Ningsih; Ihsan, Moh. (Universitas Tadulako, 2014)
Few studies have explicitly determine classification on bird community in nature reserve areas in Central Sulawesi. Here in, we reported upon the results of bird community classification, species composition and similarity index in Tinombala Nature Reserve area, Mepanga district, Parigi Moutong, Central Sulawesi.The study was conducted on may through june 2013.The birds composition was recorded by using Index Point of Abundance (IPA-count) method. Studies were conducted in four bird habitat types, i.e; along river (watershed area) ± 822m above sea level(LS: 00º 35' 38,1